Use of Polyvinyl Alcohol Sponge Cubes for Vagal Nerve Stimulation: A Suggestion for the Wrapping Step. Technical Note and Step-by-Step Operative Technique. Issue 5 (6th August 2019) - Hamdi, Hussein; Spatola, Giorgio; Lagarde, Stanislas; McGonigal, Aileen; Paz-Paredes, Armando; Bizeau, Alain; Bartolomei, Fabrice; Carron, Romain
Abstract: BACKGROUND: Vagal nerve stimulation (VNS) is an approved treatment for epilepsy and depression. Wrapping the helical electrodes around the nerve can prove technically challenging. However, a quick and efficient method to slightly elevate the nerve can highly facilitate this part of the procedure. OBJECTIVE: To provide useful surgical tips to facilitate the procedure. METHODS: Based on experience of more than 150 adult cases for mainly epilepsy (primary lead implant), the authors share their surgical technique to provide the experienced surgeons or newcomers to the field of VNS with some useful tips. All patients signed informed consent according to the local ethics committee guidelines. RESULTS: The article consists of a detailed step-by-step description of the whole procedure illustrated through high-resolution colored photographs of the surgical field. Special reference is made to the usefulness of polyvinyl alcohol (PVA) sponge cubes to elevate the nerve instead of the commonly used silicon vessel loops. CONCLUSION: The use of surgical microscope and PVA sponge cubes to elevate the nerve constitute key points to make VNS an easy surgery.